Combined analysis of miRNA‐181a with phase angle derived from bioelectrical impedance predicts radiotherapy‐induced changes in body composition and survival of male patients with head and neck cancer. Issue 9 (4th June 2019) - Powrózek, Tomasz; Brzozowska, Anna; Mazurek, Marcin; Mlak, Radosław; Sobieszek, Grzegorz; Małecka‐Massalska, Teresa
Abstract: Background: Nutritional deficits developing as an effect of applied radiotherapy (RTH) negatively affect patients' quality of life, survival, and therapy outcomes. We demonstrated novel approach to prediction of RTH‐induced changes in body composition of patients with head and neck cancer using phase angle (PA) derived from bioelectrical impedance in combination with miRNA‐181a expression. Results: Patients with simultaneous presence of low PA and high miRNA expression were at a significantly higher risk of decreasing the fat‐free mass index (FFMI) <14.9 kg/m 2 (odds ratio [OR] = 5.14; P = .02), FFM < 44.7 kg (OR = 6.20; P = .04), and lean mass (OR = 10.0; P = .04) during the therapy period. Receiver operating curve analysis allowed to predict changes in FFMI, lean mass, and FFM with area under the curve calculation over 0.700. The simultaneous presence of high miRNA and low PA negatively affected patients' survival (OR = 5.12; P = .02). Conclusion: Evaluation of PA in combination with miRNA demonstrates higher diagnostic accuracy and predictive value for detecting RTH‐induced changes in body composition of patients with cancer.